Automated decision making based on weak orderings. (1st January 2012) - Encheva, Sylvia
Ranking of help functions with respect to their usefulness is in the main focus of this work. A help function is regarded as useful to a student if the student has succeeded to solve a problem after using it. Methods from the theory of partial orderings are further applied facilitating an automated process of suggesting individualised advises on how to proceed in order to solve a particular problem. The decision making process is based on the common assumption that if given a choice between two alternatives, a person will choose one. Thus, obtained partial orderings appeared to be all linear orders since each pair of alternatives is compared. In this paper, we propose ranking help functions in an intelligent tutoring system with respect to their usefulness.